Financial Aspect Analysis of UMKM Bebek Songkem Pak Salim in Sampang Regency in Business Feasibility Study - Fawaid (Managing: Jurnal Bisnis dan Manajemen, 2025)
This research aims to analyze the financial aspects of Bebek Songkem Pak Salim MSMEs in Sampang Regency in the context of a business feasibility study. The research uses a qualitative method with a case study approach, where primary data is obtained through in-depth interviews with owners and employees as well as direct observation of operational activities and financial management of MSMEs. Secondary data is collected from financial documents such as profit and loss reports, balance sheets, and daily transaction records. The research results show that MSME Bebek Songkem Pak Salim has a stable daily income, especially during the holiday season and weekends. However, there are significant challenges in managing operational costs due to unpredictable fluctuations in raw material prices. Financial ratio analysis shows that the liquidity, solvency and profitability ratios of these MSMEs are at a fairly good level, but cash flow management still needs improvement. A quick ratio below one indicates the need for improvement in cash management. Financial projections based on historical data show that MSME Bebek Songkem Pak Salim has the potential to increase profits by up to 15% in the next two years with better financial management and effective marketing strategies. Other challenges faced by MSMEs include limited knowledge about financial management, lack of access to affordable sources of financing, and uncertainty in raw material prices. Based on the findings of this research, it is recommended that MSME owners and employees attend training on basic financial management to improve their ability to manage business finances. In addition, implementing an orderly and detailed financial recording system is very necessary to monitor cash inflows and outflows more accurately. Product diversification and increased marketing via social media and other digital platforms are expected to increase brand awareness and sales. By implementing these suggestions, it is hoped that MSME Bebek Songkem Pak Salim can improve its financial performance and make a greater contribution to the local economy in Sampang Regency.